(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The purpose of this research that, the performance budget is the best style of budget styles that can help and contribute in forming preparing federal typical budget in Iraq , By taking advantage of the application of the principles of scientific rules that would ensure optimal allocation and investment of the financial resources of the state and achieve the best performance and the lowest possible cost, both with regard to the administrative and accounting side, reducing the waste of public money, so that can enhance the success , power , and safety of financial activity of managerial system that it focuses on the magnetite and quality of the work done and the objectives wanted to meet. so application of performance budget requires making some justification on financial and accounting laws and instructions because and for make this system application success.